Implementace sdílené imigrační a azylové politiky EU na příkladu Norska a České republiky - Gyamfi, Solomon (Univerzita Pardubice, 2018)
The immigration issue has been a major problem if not the topmost in the EU recently. The four fundamental freedoms of EU law include the free movement of people within the territories of the European Union. This is ensured by creating the common condition for policies in migration. A common legal framework for immigration and asylum policies has therefore been formulated as well as the common procedure for implementing these policies by member states. However, member states do not always adhere to the EU approach in most instances adoption and disposing of the common procedure for implementing immigration and asylum policies. This result in member states seeking their national interest first which may lead to possible incompatibilities of national legislation and administrative practices with EU immigration and asylum regulations even though EU member states are guided by the primacy of EU law. Comparative analysis was done using the Czech Republic and Norway as case studies to ascertain the implementation of the Common EU immigration and asylum policy by member states. From the analysis, it was discovered that despite the attempt to achieving complete harmonization in member state's immigration and asylum policy area, there is still other national legislation which ran counter to that of the EU.
Common EU Immigration and Asylum Policy Implementation: The Case of the Kingdom of Norway and the Czech Republic
Keywords: společná přistěhovalecká politika; azylový systém; Evropská Unie; Norsko; Česká republika; národní legislativa; správní praxe; common Immigration policy; asylum system; European Union; Norway; Czech Republic; national legislation; administrative practice